Percepção ambiental do rio Paranapanema no setor da ponte pênsil Alves Lima (divisa entre os estados de São Paulo e Paraná) - Costa, Helen Patricia da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This study, supported by the methodology of Cultural and Systemic Geography, aims to raise the environmental perception in relation to the water landscape of the Paranapanema River, at the Ponte Pênsil Alves Lima (border between the States of São Paulo and Paraná). In order to comply with the objectives, the research methodology included a bibliographic review on the subject, secondary surveys, fieldwork, application of online surveys elaborated through Google Platform, tabulation and interpretation of the data. The publication of the questionnaires was through Facebook in the cities of Ourinhos/SP, Chavantes SP, and Ribeirão Claro/PR. To that extent, 42 people were interviewed for the study of environmental perception. In relation to the results of the questionnaires, all of the interviewees have visited the Ponte Pênsil Alves Lima, but most don't know any story related to it. The interviewees were also interrogated about why do they visit Paranapanema River, and 89% answered that they go to the there for their own recreation, 7% of the interviewees said they frequent the Paranapanema River for work business (marketing products), and 4% visit it for other purposes, and among them, the practice of religious rituals. In this way, the interviewees, through their perceptions, highlighted problems, concerns, and suggestions about this landscape. It is worth pointing out that some of the problems reported were observed in the fieldwork at the site, because, in the empirical experience, it was noted that there is neglect with the area, which should be preserved since it is an APP (Permanent Preservation Area). After the interpretation of the results, an informative-educational folder was produced with the aim of encouraging the population about environmental awareness, especially related to the bridge, thus contributing to the popularization of science...

O presente estudo, apoiado na metodologia da Geografia Cultural e Sistêmica, tem por objetivo levantar a percepção ambiental em relação à paisagem hídrica do Rio Paranapanema, na Ponte Pênsil Alves Lima (divisa entre os Estados de São Paulo e Paraná). Para cumprir com os objetivos, a metodologia da pesquisa contou com revisão bibliográfica sobre o tema, levantamentos secundários, trabalho de campo, aplicação de questionários online elaborado através da Plataforma Google, tabulação e interpretação dos dados. Os questionários foram publicados através da rede social Facebook nos grupos das cidades de Ourinhos/SP, Chavantes/SP e Ribeirão Claro/PR. Nesse sentido, foram entrevistadas 42 pessoas para o estudo de percepção ambiental. Em relação aos resultados do questionário, todos relataram ter visitado a Ponte Pênsil Alves Lima, porém a maioria desconhece qualquer história relacionada à mesma. Os entrevistados também foram questionados acerca do porquê visitam o Paranapanema, e 89% responderam que vão ao rio para o próprio lazer, 7% dos entrevistados disseram que frequentam o Rio Paranapanema para o trabalho (comercializar produtos), e 4% o visitam para outros fins, dentre eles, a prática de rituais religiosos. Dessa forma, os entrevistados, através de suas percepções, destacaram problemas, preocupações e sugestões acerca dessa paisagem. Vale destacar que alguns dos problemas relatados foram observados no trabaho de campo realizado no local, pois na experiência empírica, notou-se um certo descaso com a área, que deveria estar preservada, pois se trata de uma APP (Área de Preservação Permanente). Após a interpretação dos resultados, foi produzido um folder informativo-educativo com o objetivo de incentivar a população acerca da consciência ambiental, sobretudo relacionada à ponte, contribuindo assim para a popularização da ciência...
Keywords: Avaliação paisagística; Pontes; Paranapanema, Pontal do (SP)